Near-surface evaluation of Bora office area using MASW methods on land-streamer. Issue 1 (January 2021) - Muin, M R; Kurniawan, M; Musa, M D T; Winata, E; Batalipu, A I; Sahabuddin,; Alfayed, F; Marwah, S; Anjarsari, R; Maulana, M I A
Abstract: A limited seismic investigation of the Bora Office Area, was conducted using multiple seismic methods including multi-channel analysis of surface waves (MASW), using land streamer originally designed by the author. The main feature of the land streamer tool is the non-stretch woven belt on which geophone units are mounted to form a multichannel geophone array similar. As a result, it was concluded that it might be possible to avoid higher-mode contaminantion at low frequencies at sites with hight (Vs), it can be seen that the distribution of Vs values varies over the range of 240 m/s to 420 m/s. In general, can be divided into 2 layers based on the value of Vs 100 - 250 m/s as soft rock and > 250 m/s as hard rock. There is a soft rock at a depth range of 0 to 5 m with a velocity value of 140-260 m/s, and hard rock layers at a depth range of below 5m with a velocity value of 280 - 400 m s.